Assessment of anxiety levels in patients during elective upper gastrointestinal endoscopy and colonoscopy - Feyzullah ERSÖZ,; Ahmet Burak TOROS,; Gülşen AYDOĞAN,; Hasan BEKTAŞ,; Özhan ÖZCAN,; Soykan ARIKAN, (Turkish Journal of Gastroenterology, 2019)
-